Pengaruh Keberlanjutan dan Tata Kelola Perusahaan terhadap Kinerja Perusahaan dengan Reputasi Perusahaan sebagai Pemoderasi - Mayla Khoiriyah; Ramaiyanti, Sinta; Humairoh, Fitri; Afifah, Ulfa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This study aims to analyze the influence of sustainability disclosure and corporate governance on company performance by using thecompany's reputation as a moderator. The sample of this study consisted of primary and secondary sector companies listed on the Indonesia Stock Exchange, from 2014 to 2020. This study analyzes the correlation between sustainability and corporate governanceon corporate performance comprehensively through the development of corporate governance measurement instruments and uses amulti-tiered system of measurement in the disclosure of corporate sustainability This study uses Ordinary Least Square (2SLS) toanalyze data using STATA 16. The results of the study show that sustainability disclosure has a significant negative effect on the Company's performance, governance has a significant positive effect on sustainability disclosure and the Company's reputationmoderates the disclosure of sustainability and the Company's performance.